Home gardens as a predictor of enhanced dietary diversity and food security in rural Myanmar - Anu Rammohan; Bill Pritchard; Michael Dibley (BMC, 2019)
Abstract Background Home gardens have been found to improve food security and dietary diversity in a wide range of settings. However, there is a need to place home gardens within the larger food and nutrition system landscapes that shape the construction of household diets. Myanmar offers a unique opportunity to study these research questions, given the decades of political isolation, high levels of food insecurity and poor nutrition levels. Methods The aim of our paper is to use household survey data from three distinctive agro-ecological settings in rural Myanmar to empirically analyse the role of home gardens in influencing household food insecurity and dietary diversity. Our analysis is based on unique survey data conducted in rural Myanmar. The sample includes 3230 rural households from three States/Districts (Magway, Ayeyarwady and Chin). Using information on two dimensions of food security, a series of variables capturing a household's self-reported food security status and coping strategies when food is not available; and a measure of household's dietary diversity based on 24-h recall data, we empirically estimate a household's probability of being food insecure and the diversity of their diets. Results There are statistically significant associations between access to home gardens and measures of food security and improved dietary diversity. In particular, for landless households, the ownership of home gardens/ fruits and vines is statistically significant and is associated with a 6.6 percentage points lower probability of a household having to change their diet, and a 7.9 percentage points lower probability of being in hunger. Conclusions From a policy perspective, our results show that promoting home gardens among vulnerable households can improve food security and dietary diversity among vulnerable rural households in Myanmar.